Imputabilità e infermità mentale Nuovo orientamento della giurisprudenza - Ferri, Claudia; Marzano, Lorenzo; Foggia, Pierfranco (Il sogno della farfalla, 2008)
Some judicial reports related to some brutal crimes and the opinions expressed publicly by a number of experts from a variety of sectors, have led the authors to analyze the innovative position adopted recently by the Italian Magistrature on the delicate and age-old problem of the relationship between mental infirmity and criminal liability. The object in question is the sentence passed by the United Penal Sectors of the Court of Cassation of the 25 January-8 March which has finally amplified the juridic concept of “mental infirmity” to the point of including “personality disorders”, which had not hitherto impacted on a person’s liability, even though it has frequently been diagnosed in authors of atrocious crimes. Therefore, even personality disorders are now scientifically recognized as an element which can greatly undermine or exclude one’s capacity to “knowingly intend and desire” thereby diminishing criminal liability to the point of rendering a person not liable to indictment if at the time of the crime these disorders impair this capacity. A historical excursus of the legal system and forensic psychiatry, and a brief examination of the most relevant penal institutes that have constituted the basis of the sentence under examination, lead us to conclude that the latter could constitute an important departure point for a desirable opening of legal science to new acquisitions and the evolution of psychiatric science.